Dysfunction of peripheral somatic and autonomic nervous system in patients with severe forms of Crohn's disease on biological therapy with TNFα inhibitors-A single center study - Wasserbauer, Martin; Mala, Sarka; Stechova, Katerina; Hlava, Stepan; Cernikova, Pavlina; Stovicek, Jan; Drabek, Jiri; Broz, Jan; Pichlerova, Dita; Kucerova, Barbora; Liskova, Petra; Kral, Jan; et al. (PloS one, 2023)
OBJECTIVE: Crohn's disease (CD) can be associated with a wide range of extraintestinal manifestations (EIMs), including neurological ones. Published studies differ in their conclusions about the epidemiology and etiopathogenesis of neurological EIMs. The aims of this study were to demonstrate the presence and find risk factors of peripheral (somatic and autonomic) neuropathy patients with severe CD on anti-TNFα biological therapy. MATERIAL AND METHODS: A clinical examination focusing on detection of peripheral sensor-motor nervous dysfunction (including Sudoscan) and examination of autonomic nervous system dysfunction (using Ewing ́s battery tests and spectral analysis) together with laboratory tests and collection of demographic data followed by administration of questionnaires were performed on a total of 30 neurologically asymptomatic outpatients with severe CD on anti-TNFα biological therapy. RESULTS: Peripheral sensor-motor nervous function via clinical neurological examination was pathological in 36.7% and Sudoscan in 33.3% of cases. Statistically significant associations between vibration perception test and age, CD and biological therapy duration, body mass index and Crohn's Disease Activity Index were proved while statistically significant associations between temperature perception test and age and BMI were proved as well. Additionally, a decrease of total protein in a patient ́s serum below the physiological cut-off in the 6 months prior to measurement was associated with a pathological result of a Sudoscan. Cardiovascular autonomic neuropathy based on Ewing ́s battery tests was present in 56.7% of patients, no statistically significant risk factors were found. Our peripheral neuropathy questionnaire correlated with the results of the Sudoscan test and some tests of the clinical examination of peripheral sensor-motor nervous function (discriminatory contact perception test, temperature perception test). CONCLUSIONS: This study demonstrated a relatively high prevalence of peripheral (especially autonomic) neuropathy and verified some risk factors for the development of peripheral somatic neuropathy in asymptomatic patients with severe form of CD on anti-TNFα biological therapy.
Keywords: Crohnova nemoc; Autonomic Nervous System Diseases; autonomní nervový systém; TNF-alfa; Tumor Necrosis Factor-alpha; Humans; Crohn Disease; Autonomic Nervous System; lidé; nemoci autonomního nervového systému; biologická terapie; Peripheral Nervous System Diseases; Biological Therapy; nemoci periferního nervového systému